English Teaching Performance of the Beginning Teacher at High Schools in Vietnam - Bích, Trần Thị Ngọc; Tuân, Nhâm Phong (VNU Journal of Science: Education Research; Vol 30 No 4, 2014)
Abstract: This study intends to examine how well the beginning English teachers perform their job and examine the differences in satisfaction level with beginning English teachers at high schools based on characteristics such as public/non-public status and location. The framework for teaching performance was adapted from frameworks in Bransford, Darling-Hammond & LePage (2005) and Ball & Cohen (1999).  In this framework, the complex activities of teaching are divided into 24 components clustered into the following 4 domains of teaching: knowledge of subject matter and curriculum, knowledge of teaching, knowledge of learners, professional attitudes and values. The research was carried at high schools in Hanoi and Hochiminh City, two biggest cities in Vietnam. The sample size is 94 head English teachers, asked to evaluate the teaching performance of beginning English teachers in their school. T-test results show that the satisfaction level of head teachers with beginning teachers in non-public schools is higher than in public schools. The quality of beginning English teachers in non-public schools was more highly appreciated than in public schools. Keywords: Beginning teachers, high school, satisfaction.